The creative habit : learn it and use it for life : a practical guide - Tharp, Twyla; Reiter, Mark (New York : Simon & Schuster, 2006)
Whether you are a painter, musician, businessperson, or simply an individual yearning to put your creativity to use, The Creative Habit provides you with thirty-two practical exercises based on the lessons Twyla Tharp has learned in her remarkable thirty-five-year career
I walk into a white room -- Rituals of preparation -- Your creative DNA -- Harness your memory -- Before you can think out of the box, you have to start with a box -- Scratching -- Accidents will happen -- Spine -- Skill -- Ruts and grooves -- An "A" in failure -- The long run
Keywords: Creative ability; Creative thinking; Creation (Literary, artistic, etc.)